HUBUNGAN KETEBALAN LEMAK DENGAN DAYA TAHAN ATLET GULAT PELATDA JAWA TENGAH TAHUN 2015 - ono, Sulisti (Universitas Negeri Semarang, 2017)
Martial sport wrestling is one sport that uses physical contact in it?s match. But many athletes in wrestling match who have their physical condition decreased mainly endurance during the match seen from the wrestling athlete's weight. The problem in this research is how the wrestling athletes can still keep excellent durability when the game progresses through a survey fat thickness relationship with endurance athletes wrestling training center Central Java in 2015. The aim of this study was 1) to determine the relationship of the thickness of the fat with endurance athletes wrestling training center central java 2015 kardiovaskuler  2) to determine the relationship of the thickness of the fat with muscle endurance athletes wrestling training center Central Java in 2015.The method used is quantitative research methods and (one-shot) the model is a model to approach using the time of data collection by determining the variables, population, sample and sampling techniques, techniques of collecting data. The conclusion of this study is the existence of a relationship with the fat thickness endurance athletes wrestling training center Central Java in 2015.